EXTERNAL DEBT IN BOSNIA AND HERZEGOVINA – AN EMPIRICAL ANALYSIS (The South East European Journal of Economics and Business, 2020)
Over the last few decades, many countries in the world have been struggling with high indebtedness. This has been especially emphasized in periods of crisis, and this was not an exception during the last global economic crisis in 2009. The advent of the crisis has further increased the need for borrowing. Increasing indebtedness after the crisis was also characteristic of BiH economy, the country in our research focus, which had an increase of public external debt by over 100% over the last two decades.The paper focuses on the external indebtedness of Bosnia and Herzegovina (BiH) over the period 2004-2017. The empirical part relies on dynamic modelling - Vector Autoregression Model, which is used to explore total external indebtedness. The empirical investigation implies that foreign-trade exchange deficits have had the greatest impact on rising indebtedness in BiH, while movements in EURIBOR interest rates have little influence in explaining this variability. The empirical investigation implies that macroeconomic policy in BiH, if it wants to keep the external debt under control over the longer time horizon, does need to focus on deficits in its foreign exchange more. One of inevitable priorities is to work on supporting production based of export from this economy.